2020
DOI: 10.1038/s41598-020-65695-6
|View full text |Cite
|
Sign up to set email alerts
|

MIR1246 in body fluids as a biomarker for pancreatic cancer

Abstract: Pancreatic cancer is an aggressive tumor associated with poor survival, and early detection is important to improve patient outcomes. In the present study, we examined MIR1246 expression as a biomarker of pancreatic cancer. Total RNA was extracted from serum, urine and saliva samples from healthy subjects (n = 30) and patients with pancreatic cancer (n = 41, stage 0-IV). The MIR1246 level in each fluid was analyzed by quantitative reverse transcription-polymerase chain reaction. Significantly higher MIR1246 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…The sensitivity and specificity of miR-21 were 82.6 and 77.8%, and those of miR-34a were 91.3 and 77.8% for discriminating PDAC from control samples, respectively (Alemar et al, 2016). Combining both serum and urine miR-1246 levels yielded a sensitivity of 85% for the diagnosis of pancreatic cancer (Ishige et al, 2020). The expression of hsa-miR-21, hsa-miR-23a, hsa-miR-23b, and miR-29c is significantly upregulated in the saliva of pancreatic cancer patients compared to control, showing sensitivities of 71.4, 85.7, 85.7, and 57%, respectively, and 100% specificity (Humeau et al, 2015).…”
Section: Genetic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity of miR-21 were 82.6 and 77.8%, and those of miR-34a were 91.3 and 77.8% for discriminating PDAC from control samples, respectively (Alemar et al, 2016). Combining both serum and urine miR-1246 levels yielded a sensitivity of 85% for the diagnosis of pancreatic cancer (Ishige et al, 2020). The expression of hsa-miR-21, hsa-miR-23a, hsa-miR-23b, and miR-29c is significantly upregulated in the saliva of pancreatic cancer patients compared to control, showing sensitivities of 71.4, 85.7, 85.7, and 57%, respectively, and 100% specificity (Humeau et al, 2015).…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…The use of microRNAs in different types of body fluids such as urine, serum, or saliva has also been studied as biomarkers for the early detection of pancreatic cancer (Ishige et al, 2020). For example, urine miR-30e, miR-143, miR-223, and miR-204 levels and serum miR-21 and miR-34a have been proven useful as potential minimally invasive biomarkers for the diagnosis of PDAC (Debernardi et al, 2015;Alemar et al, 2016).…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…In a small British study, Debernardi et al [ 340 ] were able to demonstrate that miR-143, miR-223 and miR-30e were significantly over-expressed in patients with stage I PC compared to age-matched healthy individuals. MiR-1246 has also been assessed as a urinary biomarker, where significantly higher levels of expression were noted in patients with PC compared to controls, with an AUC of 0.90 which was superior to serum miR-1246 (AUC = 0.87)[ 18 ]. Considering the non-invasive capacity of urine sampling, coupled with the rapid expansion and interest in use of miRNA in the detection of malignancy, further studies should aim to determine whether experimental studies can translate into larger prospective clinical studies.…”
Section: Urinary Biomarkersmentioning
confidence: 99%
“…Silencing of miRs was found to be involved in ERS signaling and miRs act as effectors and modulators of the UPR and ERS pathways [48]. The miRs, isolated from human specimen, including urine, saliva, serum and tissues, are considered as biomarkers of several immune pathologies such as cancer, autoimmune diseases and viral or bacterial infections [49][50][51][52][53][54][55]. A recent study revealed miR-125b-5p to be elevated in the plasma of AE patients [56].…”
Section: Introductionmentioning
confidence: 99%